2013
DOI: 10.7314/apjcp.2013.14.11.6493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Features of Patients with Rare Ovarian Tumors: Multi-Center Review of 167 Patients by the Anatolian Society of Medical Oncology

Abstract: Non-epithelial malignant ovarian tumors (germ cell and sex cord-stromal tumors), clear cell carcinoma, Brenner tumors, transitional cell tumors, and carcinoid tumors of the ovary are defined as rare ovarian tumors (ROTs). Of these tumors, germ cell tumors (GCTs) and sex cord-stromal tumors (SCSTs) comprise approximately 15% of all ovarian malignancies, and they have a variety of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…The most common presenting symptoms in the present study were pelvic mass and pelvic pain that corresponded to a previous report which found over eighty percent of the MOGCT patients with these symptoms (Bilici et al, 2013;Matei et al, 2013). Although, dysgerminoma represented the most common type of MOGCT in the literature review (Bhurgri et al, 2011., Low et al, 2012, we found dysgerminoa was the third ranking histology in our study while the first ranking was immature teratoma and the second ranking was EST.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most common presenting symptoms in the present study were pelvic mass and pelvic pain that corresponded to a previous report which found over eighty percent of the MOGCT patients with these symptoms (Bilici et al, 2013;Matei et al, 2013). Although, dysgerminoma represented the most common type of MOGCT in the literature review (Bhurgri et al, 2011., Low et al, 2012, we found dysgerminoa was the third ranking histology in our study while the first ranking was immature teratoma and the second ranking was EST.…”
Section: Discussionsupporting
confidence: 88%
“…The most common histology is dysgerminoma followed by immature teratoma and endodermal sinus tumor (EST) (Bilici et al, 2013;Vazquez and Rustin, 2013). Moreover, MOGCT is often found in a mixed type with the most common combination of dysgerminoma and EST (Parkinson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a proliferative disorder among women of reproductive age, and currently considered a predominantly hyperandrogenic syndrome (Azziz et al, 2009;Bilici et al, 2013;, Haroon et al, 2014;Liu et al, 2013;Takiar et al, 2014a;2014b). The three main diagnostic guidelines are the 1990 National Institutes of Health (NIH) criteria (Dunaif, 1992) T2DM is a disease characterized by impaired insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian germ cell malignancy mostly occurs in the second decades of life, accounting for 5% of ovarian malignancies, and is mainly unilateral, although 10-15% of dysgerminoma involve bilaterally (Gershenson, 2007;Bilici et al, 2014). Majority of this gynecologic malignancy has been very favorable outcomes, high chemosensitivity, and long-term survival.…”
Section: Introductionmentioning
confidence: 99%